STUDY OF DRESS PERCENTAGE AND RELATIVE WEIGHTS OF CARCASS PARTS IN VARIOUS AGES OF JAPANESE QUAIL IN IRAQ - Hasan, Khalid Hamid; Ahmed, Ahmad A.; Dawood, Thana A.; Fadil, Noor K. (Diyala Agricultural Sciences Journal, 2013)
This study was conducted in Animal Resources Dept. – College of Agriculture – University of Diyala during the period 1 Feb. to 8 April 2013 , aimed to determine dress percentage , some relative weight of carcass parts( include breast , thigh and back ) , some vital organs( heart , liver ) at various ages in Japanese quail in Iraq. The study use 100 one day old chicks , the study slaughtered random sample of them consist of 70 birds , as 20 , 20 , 15 , 15 birds in 4 , 6 , 8 , 10 week of age respectively , and the measurements taken in each age and the correlation coefficients were calculated among the various measurements . The results indicated that, the age has highly significant effect in body weight , carcass weight , intestine length , also there was significant effect of age in thigh weight . The sex has significant effect in body weight , dress percentage , intestine length , liver weight , back weight , there were highly significant effect of the interaction between age and sex in body weight and carcass weight , while there was significant effect of this interaction in relative weight of liver. There were highly significant correlation coefficients among all measurements included in the study